Cocoa marketing chain in developing countries: how do formal-informal linkages ensure its sustainability in Cameroon? - Nkouedjo, L.L.; Mathé, S.; Fon, D.E.; Geitzenauer, M.; Manga, A.A. (Elsevier, 2020)
Although liberalization of the cocoa sector has increased internal competition within the marketing chain it has also led to the emergence of informal market actors within the chain. Therefore, the aim of this paper is to analyse how the cocoa marketing chain operates by measuring and comparing the marketing margins of the formal and informal actors. Qualitative data were used to establish the structure of the marketing chain and quantitative data to estimate the marketing margins. A total sampling size of 76 cocoa market actors was obtained by using a multi-stage sampling technique: 15 for qualitative data and 61 for quantitative data. Descriptive analysis was used to map the marketing chain and economic analysis to compute the costs and margins for both informal and formal market intermediaries from the Centre and South-West regions in Cameroon. The results indicated three market intermediaries (one informal and two formal) and four marketing channels by which cocoa moves from the farmers to the exporters. The calculation of marketing costs indicated that informal actors incurred the highest costs in both regions. The results regarding the marketing margins were twofold: informal actors obtain low net marketing margins when they do not use illicit strategies, but high net marketing margins when illicit strategies are used. Given the significant role of informal actors, we suggest that their actions should be integrated in a suitable manner into those of formal actors to contribute to a better performance of the marketing chain and to the sustainability of the cocoa sector.